Psycho-educational program for enhancing resilience among family caregivers of patients with leukemia in Egypt: a quasi-experimental study - gaafr, Ahmed Mohamed Mustafa; Elewa, Sahar Mahmoud Mohamed; Atta, Fatma; Adam, Shaimaa Saied (Jurnal Ners, 2025)
Introduction: Caring for a loved one with leukemia presents significant challenges and often leads to a substantial caregiver burden. Resilience, adapting and coping effectively with adversity, is crucial for caregivers’ well-being. Psychoeducational interventions incorporating coping strategies, stress management, and decision-making skills have been widely recognized to foster resilience. This study evaluated the effectiveness of a structured psychoeducational program to enhance resilience among family caregivers of patients with leukemia. Methods: This quasi-experimental pre-post study assessed the effectiveness of a psychoeducational program among 57 family caregivers of patients with leukemia at the National Cancer Institute in Egypt. The Family Resilience Assessment Scale (FRAS) was administered before and after a structured 21-session program. Data were analyzed using IBM SPSS Statistics 23, paired t-tests assessing resilience changes, and Spearman’s correlation to examine associations with demographic and psychological factors. The reliability of the FRAS was confirmed using Cronbach’s alpha (≥0.70). Results: 66.7% of caregivers were female, 36.8% were aged 25–30, 49.1% were married, and 66.7% provided care for more than eight hours daily. Statistically significant improvements (p < 0.01) were observed in communication, emotional expression, problem solving, resource utilization, maintaining a positive outlook, family connectedness, spirituality, meaning making, and flexibility after the intervention. Conclusions: The psychoeducational program significantly improved resilience among family caregivers of patients with leukemia. These findings highlight the importance of integrating such interventions into caregiver support programs to reduce stress and promote well-being. Future studies should examine the long-term sustainability of these benefits.